Awareness of Cervical Cancer and Its Risk Factors Among Gynaecology Clinic Attendees - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background and Aims:Death from cervical cancer is preventable through effective cervical cancer screening and treatment of premalignant disease. Several studies have identified the lack of awareness and inadequate knowledge about cervical cancer among barriers to prevention of cervical cancer. Determining the level of awareness of cervical cancer may inform strategies that could empower women with adequate knowledge on cervical cancer and its prevention. This study aims at determining the level of awareness of cervical cancer and its risk factors among Gynaecology clinic attendees.Methods:The study was conducted in the State Specialist Hospital Damaturu, from July 2017 to May 2018. It was a descriptive cross sectional study conducted among 200 Gynae -clinic attendees, aged 15-60 years. The researchers administered structured questionnaires to obtain the data.Results:Of the 200 women interviewed, only 46 (23%) of them heard of cervical cancer. The radio (media) was the commonest source of information in majority (93%) of those that were aware of cervical cancer. 75% of the respondents did not know most of the risk factors of cervical cancer.Conclusion:The knowledge of cervical cancer and its risk factors was generally poor among the respondents. The media especially the radio could play an important role in raising awareness on cervical cancer.